Evaluation of quality of distance courses adapted by students - Vinogradova, Irina; Kurilovas, Eugenijus (Lietuvos matematikos rinkinys, 2010)
Several distance learning courses adaptation aspects are analyzed in the paper. Adaptation characteristics of virtual learning environments and distance learning courses are considered very significant quality factors in scientific literature. These factors warrant the better adaptability of distance learning courses to the different learners’ needs, and therefore, the better learning quality. While creating distance learning courses according to “Computer training systems” teaching program for VGTU IV course students, there was an additional course adaptation requirement for the students. The aim of this paper is to analyze the students’ works from courses’ adaptation point of view. The paper is also aimed to analyze which course sequencing rules are the mostly clear and often used by the students.